Dysregulation of Intestinal Physiology by Aflatoxicosis in the Gilthead Seabream (Sparus aurata) - Barany, Andre; Oliva, Milagrosa; Gregório, Silvia Filipa; Martínez-Rodríguez, Gonzalo; Mancera, Juan Miguel; Fuentes, Juan (Frontiers in Physiology, 2021)
Aflatoxin B1 (AFB1) is a mycotoxin often present in food. This study aimed to understand the physiological effects of AFB1 on the seabream (Sparus aurata) gastrointestinal system. In a first in vitro approach, we investigated ion transport using the short-circuit current (Isc) technique in Ussing chambers in the anterior intestine (AI). Application of apical/luminal AFB1 concentrations of 8 and 16 µM to healthy tissues were without effect on tissue transepithelial electrical resistance (TER), and apparent tissue permeability (Papp) measured using fluorescein FITC (4 kD). However, it resulted in dose-related effects on Isc. In a second approach, seabream juveniles fed with different AFB1 concentrations (1 and 2 mg AFB1 kg-1 fish feed) for 85 days showed significantly reduced gill Na+/K+-ATPase (NKA) and H+-ATPase (HA) activities in the posterior intestine (PI). Moreover, dietary AFB1 modified Isc in the AI and PI, significantly affecting TER in the AI. To understand this effect on TER, we analyzed the expression of nine claudins and three occludins as markers of intestinal architecture and permeability using qPCR. Around 80 % of the genes presented significantly different relative mRNA expression between AI and PI and had concomitant sensitivity to dietary AFB1. Based on the results of our in vitro, in vivo, and molecular approaches, we conclude that the effects of dietary AFB1 in the gastrointestinal system are at the base of the previously reported growth impairment caused by AFB1 in fish.